SIMULTANEOUS ACTION OF THE FLAVONOID QUERCETIN ON CYTOCHROME P450 (CYP) 1A2, CYP2A6, N-ACETYLTRANSFERASE AND XANTHINE OXIDASE ACTIVITY IN HEALTHY VOLUNTEERS - Chen, Yao; Xiao, Peng; Ou-Yang, Dong-Sheng; Fan, Lan; Guo, Dong; Wang, Yi-Nan; Han, Yang; Tu, Jiang-Hua; Zhou, Gan; Huang, Yuan-Fei; Zhou, Hong-Hao (Clinical and experimental pharmacology & physiology, 2009)
SUMMARY 1 Quercetin, one of the most abundant natural flavonoids, has been reported to modulate the activity of several drug‐metabolising enzymes. The aim of the present study was to investigate the effects of quercetin on cytochrome P450 (CYP) 1A2, CYP2A6, N‐acetyltransferase (NAT2) and xanthine oxidase (XO) activity in healthy volunteers using caffeine as a probe drug. 2 Twelve unrelated, healthy volunteers were recruited to the study. There were two phases to the study; in the first phase, each subject was given a single oral dose of caffeine (one 100 mg capsule) with 150 mL water; in the second phase, each subject was give a 500 mg quercetin capsule once daily for 13 continuous days and was coadministered a 100 mg caffeine capsule on the 13th day. Urinary caffeine metabolite ratios were used as indicators of the activity of CYP1A2, CYP2A6, NAT2 and XO. The pharmacokinetics of caffeine and its metabolites were determined by HPLC. 3 In the quercetin‐treated group, CYP1A2 activity was decreased by 10.4% (95% confidence interval (CI), 1.1–29.8%; P = 0.039), whereas increases were observed in CYP2A6 (by 25.3%; 95% CI, 6.2–34.5%; P = 0.002), NAT2 (by 88.7%; 95% CI, 7.1–160.2%; P = 0.010) and XO activity (by 15.0%; 95% CI, 1.6–21.6%; P = 0.007). Plasma Cmax and the AUC(0–24 h) of 1,7‐dimethylxanthine were decreased by 17.2% (95% CI, 6.4–28.0%; P = 0.024) and 16.2% (95% CI, 3.9–28.5%; P = 0.032), respectively. The urinary excretion of 1,7‐dimethylxanthine and 1‐methylxanthine was significantly decreased by 32.4% (95% CI, 2.5–62.1%; P = 0.036) and 156.1% (95% CI, 53.3–258.9%; P = 0.004), respectively. The urinary excretion of 1,7‐dimethylurate and 1‐methylurate was increased by 82.9% (95% CI, 56.0–165.4%; P = 0.030) and 97.8% (95% CI, 12.1–183.5%; P = 0.029), respectively. No changes were observed in the urinary excretion of caffeine and 5‐acetylamino‐6‐formylamino‐3‐methyluracil between the two study phases. 4 The results of the present study indicate that quercetin inhibits CYP1A2 function, but enhances CYP2A6, NAT2 and XO activity. Simultaneously, some pharmacokinetic parameters relating to 1,7‐dimethylxanthine were affected by quercetin. Thus, we conclude that quercetin affects CYP1A2, CYP2A6, NAT2 and XO activity in vivo.